Ikonografija emblemov v Spominski knjigi ljubljanske plemiške družbe sv. Dizma - Germ, Tine (Knjižnica, 2011)
Purpose: The Album of the Ljubljana Noble Society of St Dismas is the most important illuminated manuscript of the Baroque era in Slovenia. It is of special interest also because it contains many interesting emblems. Until recently it has been known only to a few specialists. It was only in 1998, when the great project of the Facsimile was undertaken, that scholars started to pay due attention to this treasure of Baroque illumination and emblematics. For the first time the illuminations were systematically examined and an attemp was made to interpret their iconography. But unfortunately the iconographic catalogue to the Facsimile offers only basic descriptions. It does not provide sufficient analysis of the emblems and often the interpretation is inadequate. Methodology/approach: the article represents a case-study concentrating on the iconography of animals depicted in the emblems of the Album of the Ljubljana Noble Society of St Dismas. Results: the article points out the misconceptions in the interpretation of individual emblems in the Album of the Ljubljana Noble Society of St Dismas and brings a new, more adequate explanation. Research limitation: for a more thorough presentation of the emblems in the Album a detailed iconographic analysis of the miniatures should be undertaken. Originality/practical implications: the article develops an iconographic/iconological method of contextual analysis of baroque emblems which introduces a new understanding of the emblems in the Album of the Ljubljana Noble Society of St Dismas. It also points out methodological misconceptions in earlier interpretations.
Keywords: Album of the Ljubljana Noble society of St Dismas; rokopisi; Spominska knjiga ljubljanske plemiške družbe sv. Dizma; baroque emblematics; emblemi; animal symbolism; iconography; ikonografija; barok